2006
DOI: 10.1002/pros.20360
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor production in human prostate cancer cells is stimulated by overexpression of platelet 12-lipoxygenase

Abstract: Our data provide insight into a possible mechanism by which prostate cancer cells with elevated expression of P12-LOX stimulate VEGF production, thus increasing their angiogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…In prostate cancer cells, this has been reported by two independent groups [38,83]. Both NDGA and baicalein reduced VEGF expression, confirming that the enzymatic activity of 12-LOX plays a significant role in the regulation of VEGF gene expression.…”
Section: Regulation Of Tumor Cell Death By Loxsupporting
confidence: 64%
“…In prostate cancer cells, this has been reported by two independent groups [38,83]. Both NDGA and baicalein reduced VEGF expression, confirming that the enzymatic activity of 12-LOX plays a significant role in the regulation of VEGF gene expression.…”
Section: Regulation Of Tumor Cell Death By Loxsupporting
confidence: 64%
“…12S-HETE also increased the release of another proangiogenic molecule, VEGF, from prostate tumor cells, whereas 12-LO inhibitors had the opposite effect, suggesting that 12S-HETE is an endogenous regulator of VEGF secretion by these cells [153]. Overexpression of 12-LO had a similar effect [141,153]. …”
Section: Biological Actions Of Hetes and Oxoetesmentioning
confidence: 99%
“…Studies of tumor xenografts in mice, demonstrated that prostate tumors generated from 12-LOX overexpressing prostate cancer PC-3 cells were of a highly angiogenic phenotype [9]. This phenomenon was later attributed to the enhanced secretion of VEGF induced by 12-LOX in prostate cancer cells [8, 12]. …”
Section: Introductionmentioning
confidence: 99%